2006
DOI: 10.1158/1055-9965.epi-06-0063
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Inhibitory Cytokine-1 H6D Polymorphism, Prostate Cancer Risk, and Survival

Abstract: Macrophage inhibitory cytokine-1 (MIC-1), a member of the transforming growth factor-B superfamily, is important in regulating inflammation. Inflammation of the prostate has been suggested to favor tumor development. A recent study (JNCI 2004(JNCI , 96:1248(JNCI -1254 found marginal evidence of an association between the presence of the mature MIC-1 protein nonsynonymous polymorphism H6D C-to-G (rs1058587) with reduced prostate cancer risk [odds ratio, 0.83; 95% confidence interval (95% CI), 0.69-0.99]. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 12 publications
3
20
0
Order By: Relevance
“…For the previously associated H6D polymorphism, the allele frequency among Caucasians (controls/cases, 27.2%/ 26.5%) was similar to the Swedish (controls/cases, 28.8%/ 27.7%) and Australian (controls/cases, 26.5%/24.3%) studies (1,2). Our analysis detected a statistically nonsignificant inverse association between the H6D polymorphism and prostate cancer risk (CG/GG versus CC; OR, 0.85; 95% CI, 0.66-1.09; P = 0.20).…”
Section: Mic1supporting
confidence: 74%
See 3 more Smart Citations
“…For the previously associated H6D polymorphism, the allele frequency among Caucasians (controls/cases, 27.2%/ 26.5%) was similar to the Swedish (controls/cases, 28.8%/ 27.7%) and Australian (controls/cases, 26.5%/24.3%) studies (1,2). Our analysis detected a statistically nonsignificant inverse association between the H6D polymorphism and prostate cancer risk (CG/GG versus CC; OR, 0.85; 95% CI, 0.66-1.09; P = 0.20).…”
Section: Mic1supporting
confidence: 74%
“…We did observe a nonsignificant inverse association between the MIC1 H6D polymorphism and prostate cancer as seen in the Australian study (1). To further clarify this effect, we genotyped the H6D polymorphism in a sibling study of 439 prostate cancer cases and 479 unaffected brothers (f90% White, 9% African American, and 1% Asian or Latino; ref.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The H6D form of GDF-15 has potential clinical relevance, as several studies indicated better prognosis in prostate cancer (PCa) patients carrying the G allele (H6D protein) than those with wild-type GDF-15. 11,12 According to the Hardy --Weinberg equilibrium, the genotype frequencies in the healthy population were estimated to be 54% for homozygotes containing only histidine (alleles CC), 7% for aspartic acid homozygotes (GG) and 39% for heterozygotes (CG). subsequent proteasomal degradation of the incorrectly folded GDF-15 precursor.…”
Section: Gdf-15 Sequence and Structurementioning
confidence: 99%